Juridical Review of Illegal Logging (Illegal Logging) Judging from Law No. 42 of 1999 concerning Forestry: Tinjauan Yuridis Terhadap Penebangan Hutan Secara Liar (Ilegal Logging) Ditinjau dari UU No 42 Tahun 1999 tentang kehutanan - Gulo, Fedieli (UPMI Proceeding Series, 2023)
Law Number 41 of 1999 concerning Forestry and Presidential Instruction Number 4 of 2005 concerning the Eradication of Illegal Logging in Forest Areas and Their Distribution in All Regions in Indonesia. This regulation emphasizes to every community that forests are very important for human survival and for future generations. Therefore, everyone is prohibited from carrying out illegal logging actions which are unlawful or criminal acts that are detrimental to the state and also the lives of many people. In this study is a qualitative analysis. Qualitative analysis is an analysis in the form of parsing sentences using a deductive line of thinking, namely drawing specific conclusions based on general rules regarding illegal logging.